Thiol-stabilized atomically precise, superatomic silver nanoparticles for catalysing cycloisomerization of alkynyl amines. Issue 5 (12th March 2018) - Yan, Juanzhu; Zhang, Jun; Chen, Xumao; Malola, Sami; Zhou, Bo; Selenius, Elli; Zhang, Xiaomin; Yuan, Peng; Deng, Guocheng; Liu, Kunlong; Su, Haifeng; Teo, Boon K; et al.
Abstract: Both the electronic and surface structures of metal nanomaterials play critical roles in determining their chemical properties. However, the non-molecular nature of conventional nanoparticles makes it extremely challenging to understand the molecular mechanism behind many of their unique electronic and surface properties. In this work, we report the synthesis, molecular and electronic structures of an atomically precise nanoparticle, [Ag206 L72 ] q (L = thiolate, halide; q = charge). With a four-shell Ag7 @Ag32 @Ag77 @Ag90 Ino-decahedral structure having a nearly perfect D5h symmetry, the metal core of the nanoparticle is co-stabilized by 68 thiolate and 4 halide ligands. Both electrochemistry and plasmonic absorption reveal the metallic nature of the nanoparticles, which is explained by density functional theory calculations. Electronically, the nanoparticle can be considered as a superatom, just short of a major electron shell closing of 138 electrons ( q = –4). More importantly, many of ligands capping on the nanoparticle are labile due to their low-coordination modes, leading to high surface reactivity for catalysing the synthesis of indoles from 2-ethynylaniline derivatives. The results exemplify the power of the atomic-precision nanocluster approach to catalysis in probing reaction mechanisms and in revealing the interplay of heterogeneous reactivities, electronic and surface structural dynamics, thereby providing ways for optimization.